The incomplete glutathione puzzle: just guessing at numbers and figures? - Deponte, Marcel (Antioxidants & redox signaling, 2017)
Signiﬁcance: Glutathione metabolism is comparable to a jigsaw puzzle with too many pieces. It is supposed to comprise (i) the reduction of disulﬁdes, hydroperoxides, sulfenic acids, and nitrosothiols, (ii) the detoxiﬁcation of aldehydes, xenobiotics, and heavy metals, and (iii) the synthesis of eicosanoids, steroids, and iron-sulfur clusters. In addition, glutathione affects oxidative protein folding and redox signaling. Here, I try to provide an overview on the relevance of glutathione-dependent pathways with an emphasis on quantitative data.